2018
DOI: 10.3201/eid2406.172071
|View full text |Cite
|
Sign up to set email alerts
|

Reassortant Clade 2.3.4.4 of Highly Pathogenic Avian Influenza A(H5N6) Virus, Taiwan, 2017

Abstract: A highly pathogenic avian influenza A(H5N6) virus of clade 2.3.4.4 was detected in a domestic duck found dead in Taiwan during February 2017. The endemic situation and continued evolution of various reassortant highly pathogenic avian influenza viruses in Taiwan warrant concern about further reassortment and a fifth wave of intercontinental spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The evidences supporting migratory birds play an important role in introducing novel HPAI subtypes into Taiwan was provided as the following. First, all four subtypes of H5Nx identified during 2015–2017 shared the same HA gene lineage derived from A/goose/Guangdong/1/96-like (Gs/GD) HPAI H5, which has never been identified before in Taiwan [ 18 , 19 ]. Phylogenetic analyses, based on influenza HA genes, demonstrated that HPAI H5Nx viruses isolated in poultry farms during the first wave in Taiwan were closely related to two Japanese isolates identified from wild birds in late 2014 ( S6A and S6B Fig ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidences supporting migratory birds play an important role in introducing novel HPAI subtypes into Taiwan was provided as the following. First, all four subtypes of H5Nx identified during 2015–2017 shared the same HA gene lineage derived from A/goose/Guangdong/1/96-like (Gs/GD) HPAI H5, which has never been identified before in Taiwan [ 18 , 19 ]. Phylogenetic analyses, based on influenza HA genes, demonstrated that HPAI H5Nx viruses isolated in poultry farms during the first wave in Taiwan were closely related to two Japanese isolates identified from wild birds in late 2014 ( S6A and S6B Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Three subtypes of HPAI virus, including Eurasian lineage of H5N2, H5N8 and H5N3, were detected unprecedentedly during the same wave of outbreaks [ 18 ]. In 2017, a second wave of HPAI poultry farm outbreaks occurred and a new subtype, H5N6, was detected [ 19 ]. Even though all the necessary control measures were implemented during the outbreaks in Taiwan, two new subtypes of H5Nx, H5N2 and H5N8, were shown to be particularly difficult to eliminate.…”
Section: Introductionmentioning
confidence: 99%
“…These emergent H5 viruses included the Eurasian lineage of H5N2, H5N8 and H5N3, which all caused high mortality in geese [ 7 ]. Soon after this episode, another novel HPAIV (H5N6) was detected in a dead duck, and this strain caused sporadic outbreaks throughout 2017 [ 8 ]. Such continuous evolution and emergence of new subtypes along with sustained transmission of AIVs in the domestic poultry industry creates a need to continuously monitor the status of H5 epidemics and to better understand the pathogenic mechanisms of these viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Of much concern,2.3.4.4 H5N8 and 2.3.4.4 H5N6 viruses of this "H5Nx" complex have become predominant and been diversifying into four distinct genetic groups, A, B, C, and D of worldwide dispersion (Bi et al, 2016;Lee et al, 2017;Si et al, 2017). Group A and B comprising H5N8 emerged in countries of North Asia and North America (Japan, Korea, Taiwan, China, Canada, the United States) in 2013-2015 are moving to Europe in recent years (Pohlmann et al, 2019;King et al, 2020); Group C and D of H5N1 and H5N6 viruses were identified in China, Laos, Vietnam in 2013-2014, recently in Vietnam, Japan, Korea, Taiwan, and Russia (Lee et al, 2017;Chen et al, 2017;Takemae et al, 2017;Nguyen et al, 2017;Nguyen et al, 2019a, b;Susloparov et al, 2019;Baek et al, 2020). According to the number of H5N6 viruses clustered in each group, Group C and Group D are designated as Major and Minor groups in the phylogenetic tree construction (Bi et al, 2016;Takemae et al, 2017).…”
Section: Introductionmentioning
confidence: 99%